Interface Conversacional para domótica - Ricardo Jorge da Rocha Loureiro (2017)
Home automation is an area that is seeing a lot of development and resources dedicated to in the past few years. Many devices nowadays are constantly connected to the Internet (IoT) and this is a huge opportunity to create a software application that can manage them all. There were a lot of experiments, many of them with recognizable success, in creating the right software to manage these devices but none that succeeds completely. This is due to the overwhelming complexity and the difficulty of use. The purpose of having an IoT environment at home is to aim for comfort and ease of management, not to being constantly challenged or having the necessity of monitoring them all the time.The main focus is to create a chat interface that allows the users to interact with their systems at home in their most used applications (reaching the users where they already are, like Facebook), creating something that not only allows you to control and manage your home automation systems but also something that gives you the right information at the right time by pattern detection or some behavior deviations. To test the developed product it will be used a domotics system already created by WIT Software and the MVP will be presented to the market afterwards.The number of connected devices is expected to grow from 9 billion in 2011 to 24 billion in 2020. The opportunities to take on IoT are proliferating and this is the perfect time for the perfect technology, the market is aching for it.